Impact of climate change on rural peasant farming: a case of Guruve (2014). - Maraya, Tinashe F. (Midlands State University, 2017)
Climate change is a topical issue which has captured many researchers attention recently. The research was carried out in the Guruve Rural District Council in Mashonaland province. The researcher wanted to know and fully understand how climate change has affected farmers in this area. The researcher used the qualitative research method were she made use of questionnaire and interviews from the findings, the researcher found out that climate change has brought about many effects on rural peasant farming some of these being water scarcity, immature crop yields and loss of livestock and health complications. Farmers have already started to note differences and have started to implement adaptation measures such as conservation farming, water harvesting and the cultivating of small grain crops.